The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5nr00505a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anatase and rutile titanium dioxide nanoparticles on uptake carriers and efflux pumps in Caco-2 gut epithelial cells

Abstract: TiO2 microparticles are widely used in food products, where they are added as a white food colouring agent. This food additive contains a significant amount of nanoscale particles; still the impact of TiO2 nanoparticles (TiO2-NPs) on gut cells is poorly documented. Our study aimed at evaluating the impact of rutile and anatase TiO2-NPs on the main functions of enterocytes, i.e. nutrient absorption driven by solute-liquid carriers (SLC transporters) and protection against other xenobiotics driven by efflux pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 52 publications
(122 reference statements)
7
38
0
Order By: Relevance
“…Ultra-thin sections were cut (80 nm), counterstained with uranyl acetate and observed with a JEOL 1200 EX transmission electron microscope (TEM) operated at 80 kV (Grenoble Institut des Neurosciences, France) [35].…”
Section: Electron Microscopymentioning
confidence: 99%
“…Ultra-thin sections were cut (80 nm), counterstained with uranyl acetate and observed with a JEOL 1200 EX transmission electron microscope (TEM) operated at 80 kV (Grenoble Institut des Neurosciences, France) [35].…”
Section: Electron Microscopymentioning
confidence: 99%
“…As NPs in food are present in mixtures with food matrices containing carbohydrates, proteins, lipids, minerals, and other trace elements, interactions between NPs and food components can be critical factors affecting potential toxicity, oral absorption, biodistribution, and efficacy of NPs. It was reported that NPs affect nutrient absorption (Mahler et al, 2012; Dorier et al, 2015), but the interactions between food-grade NPs and food components have not been well explored. On the other hand, food components could also influence the absorption and toxicity of NPs as well (Wang et al, 2014; Bohmert et al, 2015; Docter et al, 2015; Lichtenstein et al, 2015; Jiang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[67][68][69][70][71] The ability of TiO 2 nanoparticles to exhibit these toxic effects has been attributed to numerous mechanisms, including generation of ROS species that damage key cellular constituents, interference with efflux pumps and nutrient transporters, induction of inflammation, and alteration of the gut microbiota. 12,72,73 Anatase TiO 2 nanoparticles were reported to be more toxic to cells than rutile nanoparticles due to their higher photo-catalytic activity. 74 A cell culture study showed that a mixture of anatase and rutile forms caused more severe cytotoxic and genotoxic damage than pure anatase or pure rutile titanium dioxide nanoparticles.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…12,72,73 Anatase TiO 2 nanoparticles were reported to be more toxic to cells than rutile nanoparticles due to their higher photo-catalytic activity. 74 A cell culture study showed that a mixture of anatase and rutile forms caused more severe cytotoxic and genotoxic damage than pure anatase or pure rutile titanium dioxide nanoparticles. 75 However, this result is in contrast to another animal study where a mixture of anatase and rutile forms of TiO 2 nanoparticles did not cause significant toxicity in rats.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%